Blake Leyerle, "The Narrative Shape of Emotion in the Preaching of John Chrysostom", Christianity in Late Antiquity 10, University of California Press, Oakland (California) 2020, ss. 213 - Szczur, Piotr (Vox Patrum, 2024)
Review of the book: Blake Leyerle, The Narrative Shape of Emotion in the Preaching of John Chrysostom, Christianity in Late Antiquity 10, University of California Press, Oakland (California) 2020.